Pengaruh Pemberian Kombinasi Jahe Merah, Bawang Putih, Apel, Lemon Dan Madu Terhadap Kadar Kolesterol Total Dan Histopatologis Pembuluh Darah Aorta Jantung Tikus Putih Jantan - Ifora Ifora; Surya Dharma; Diken Maywidia Darma (STIFARM Padang, 2016)
Study of the effect of red ginger (Zingiber officinale Roscoe), garlic (Allium sativum L.), apple (Malus domestica Borkh.), Lemon (Citrus limon (L.) Osbeck and honey have been carried out on total cholesterol levels by using the tool Easy Touch GCHb and histopathologic examination aorta in male rats.The combination dosage were given orally for 28 days with a dose of red ginger 0.162 g / 200 g, garlic 0.09 g / 200 g, apples 1.8 g / 200 g, lemon 50 mL / 200 g, and the honey of 1.8 g/ 200 g. The data were analyzed by one-way ANOVA followed by Duncan test.The results showed a decrease in total cholesterol levels may affect histopathologic aorta is extensive aortic lumen of blood vessels and blood vessel damage scores were significant (P <0.05), which means the provision of a combination of red ginger (Zingiber officinale Roscoe), garlic (Allium sativum L.), apple (Malus domestica Borkh.), lemon (Citrus limon (L.) Osbeck and honey can lower total cholesterol and improve lumen area and lower scores damage to the blood vessels.